SP_Ace: a new code to estimate Teff, log g, and elemental abundances - Boeche, Corrado (Astronomische Nachrichten, 2016)
SP_Ace is a FORTRAN95 code that derives stellar parameters and elemental abundances from stellar spectra. To derive these parameters, SP_Ace does not measure equivalent widths of lines nor it uses templates of synthetic spectra, but it employs a new method based on a library of General Curve-Of-Growths. To date SP_Ace works on the wavelength range 5212-6860 Å and 8400-8921 Å, and at the spectral resolution R = 2000-20000. Extensions of these limits are possible. SP_Ace is a highly automated code suitable for application to large spectroscopic surveys. A web front end to this service is publicly available at http://dc.g-vo.org/SP_ACE together with the library and the binary code.